Chernobyl Exclusion Zone as a tourist attraction - Bryś, Mateusz (Who needs tourism?, 2024)
The aim of the article is to present the development of tourism in the Chernobyl Exclusion Zone and to answer the question why this place has become a tourist attraction. A form of tourism called ‘dark tourism’ will be described. Then the effects of the disaster at the Chernobyl power plant and how this event has become the basis for the transformation of the Chernobyl zone into a tourist attraction will be presented. By analysing research on those who have travelled to Chernobyl, the type of tourist and their motivations for travelling to the exclusion zone will be given. Statistical data showing the development of tourism is analyzed and the offers of travel agencies presented. Specific rules related to traveling to this place are also described.